Attitudes toward Family Obligations among American Adolescents with Asian, Latin American, and European Backgrounds - Fuligni, Andrew J.; Tseng, Vivian; Lam, May (Child development, 1999)
This study was designed to examine the attitudes toward family obligations among over 800 American tenth (M age = 15.7 years) and twelfth (M age = 17.7 years) grade students from Filipino, Chinese, Mexican, Central and South American, and European backgrounds. Asian and Latin American adolescents possessed stronger values and greater expectations regarding their duty to assist, respect, and support their families than their peers with European backgrounds. These differences tended to be large and were consistent across the youths' generation, gender, family composition, and socioeconomic background. Whereas an emphasis on family obligations tended to be associated with more positive family and peer relationships and academic motivation, adolescents who indicated the strongest endorsement of their obligations tended to receive school grades just as low as or even lower than those with the weakest endorsement. There was no evidence, however, that the ethnic variations in attitudes produced meaningful group differences in the adolescents' development. These findings suggest that even within a society that emphasizes adolescent autonomy and independence, youths from families with collectivistic traditions retain their parents' familistic values and that these values do not have a negative impact upon their development.